1976
DOI: 10.1128/iai.13.5.1315-1320.1976
|View full text |Cite
|
Sign up to set email alerts
|

Experimental group B streptococcal infections in mice: hematogenous virulence and mucosal colonization

Abstract: A group B streptococcus recovered from a blood specimen from a neonate with sepsis was used to evaluate the use of mice for studies characterizing the hematogenous virulence and the asymptomatic mucosal colonization of the vagina or of the respiratory tract by these bacteria. When injected intravenously, the 50% lethal dose for mice was 106; however, as few as 102 organisms produced septic deaths. In mice undergoing water diuresis, bacteriuria and pyelonephritis were not produced after direct bladder inoculati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1978
1978
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Animal models of vaginal colonization have been developed with three main aims: investigating GBS factors involved in host interaction that may favor bacterial acquisition and persistence 11 14 , elucidating host innate immune responses 13 , 15 and identifying potential preventive strategies 16 – 18 . By these models, it has been demonstrated that GBS carriage induces infiltration of lymphocytes and the production of soluble inflammatory mediators in the vaginal mucosa, and that GBS bacteria can persist in the genital tract for long periods by subverting innate immune defenses.…”
Section: Introductionmentioning
confidence: 99%
“…Animal models of vaginal colonization have been developed with three main aims: investigating GBS factors involved in host interaction that may favor bacterial acquisition and persistence 11 14 , elucidating host innate immune responses 13 , 15 and identifying potential preventive strategies 16 – 18 . By these models, it has been demonstrated that GBS carriage induces infiltration of lymphocytes and the production of soluble inflammatory mediators in the vaginal mucosa, and that GBS bacteria can persist in the genital tract for long periods by subverting innate immune defenses.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have successfully employed the mouse lethality test as a model for study of disease due to GBS (7,9,11,14,16). However, certain parameters of the model have not yet been delineated.…”
Section: Discussionmentioning
confidence: 99%
“…Antibody to GBS has been detected by functional assays of immunity which include opsonization (1, 6, 10, 12, 14,), chicken embryo protection (15), and mouse protection tests (7,11,14). Several authors have described the similarity of the pathology of GBS infection of mice to that of humans (9,16). Until recently, the mouse model had been utilized only for the study of GBS serotypes Ia, Ib, Ic, and II because of the inability to cause lethal disease in mice with serotype III strains (2,14,15).…”
mentioning
confidence: 99%
“…In the study of the pathogenesis of this disease, several animal models have been developed. These include a chicken embryo model (20), an adult mouse model (22), a newborn mouse model (10), and a newborn rat model (7,9). The design of these models allows the study of the natural history, progression, and pathology of group B streptococcal disease but gives limited information concerning its epidemiology.…”
Section: Cp>010mentioning
confidence: 99%
“…The design of these models allows the study of the natural history, progression, and pathology of group B streptococcal disease but gives limited information concerning its epidemiology. The mouse model described by Furtado (10) demonstrated that group B streptococci could colonize mucosal surfaces, such as vagina and pharynx, of these rodents, but there was no investigation of neonatal acquisition (in contrast to disease) or of mother-infant transmission of group B streptococci.…”
Section: Cp>010mentioning
confidence: 99%